2023
DOI: 10.3390/ijms241512189
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Human Rotaviruses in Wuhan, China (2019–2022): Whole-Genome Analysis of Emerging DS-1-like G8P[8] Rotavirus

Xuan Zhou,
Yuanhong Wang,
Nan Chen
et al.

Abstract: Group A rotaviruses (RVAs) are major etiologic agents of gastroenteritis in infants and young children worldwide. To study the prevalence and genetic characteristics of RVAs, a hospital-based surveillance study was conducted in Wuhan, China from June 2019 through May 2022. The detection rate of RVAs was 19.40% (142/732) and 3.51% (8/228) in children and adults, respectively. G9P[8] was the predominant genotype, followed by G8P[8] and G3P[8]. G8P[8] emerged and was dominant in the 2021–2022 epidemic season. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Reassortment and mutation have a major impact on the evolution of rotavirus and the emergence of new strains 23 . The complete genotypes of G8P[8] strain circulating in Beijing was “G8‐P[8]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2.” This strain was formed by multiple reassortment events between the DS‐1‐like strains and a bovine‐like G8 genotype (DS‐1‐like G8P[8] strain) 23,24 . G8P[8] was also detected in other regions of China from 2020 to 2022, such as Fuzhou, Guangzhou, Wuhan, and Shanghai, which also became the predominant strain in children in Shanghai in 2022 and is highly similar to the strains in our study 25–28 .…”
Section: Discussionsupporting
confidence: 73%
“…Reassortment and mutation have a major impact on the evolution of rotavirus and the emergence of new strains 23 . The complete genotypes of G8P[8] strain circulating in Beijing was “G8‐P[8]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2.” This strain was formed by multiple reassortment events between the DS‐1‐like strains and a bovine‐like G8 genotype (DS‐1‐like G8P[8] strain) 23,24 . G8P[8] was also detected in other regions of China from 2020 to 2022, such as Fuzhou, Guangzhou, Wuhan, and Shanghai, which also became the predominant strain in children in Shanghai in 2022 and is highly similar to the strains in our study 25–28 .…”
Section: Discussionsupporting
confidence: 73%
“…It has been detected in children in many countries and has become one of the dominant strains in some sub‐Saharan African countries 11 . Data from studies in Beijing and Wuhan showed that a high proportion of children with AGE were infected with G8 RVA recently 9,10 . Altogether, the data indicate that G8 will be likely replace G9 as the predominant G genotype among RVA‐infected children with AGE in China.…”
Section: Discussionmentioning
confidence: 95%
“…11 Data from studies in Beijing and Wuhan showed that a high proportion of children with AGE were infected with G8 RVA recently. 9,10 Altogether, the data indicate that G8 will be likely replace G9 as the predominant G genotype among RVA-infected children with AGE in China. This hypothesis needs to be supported by more comprehensive epidemiological data on RVA in different regions of China.…”
Section: Sequence Analysis Of Vp7 Segments Deserved To G8 Genotypementioning
confidence: 93%
See 2 more Smart Citations